TATAKELOLA KOMUNITAS PENANGGAP DAN PERGELARAN WAYANG JEKDONG KI SURWEDI JAWA TIMUR - , Wisma Nugraha CH.R., Drs.,M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research showcases problems in the management of commissionersâ community and Wayang JÃ¨kdong performances with the case study on Ki Surwedi. Ki Surwedi is the gateway to the understanding of Wayang JÃ¨kdong performances and art management. The research aims to describe cultural phenomenon of Wayang JÃ¨kdong by Ki Surwedi in its relation to the commissioners, audiences, and various social institutions from the village to the regional level. Etnographic methodology was employed to observe the commissioner groups and audiences of Wayang JÃ¨kdong. A field study or grounded research is done to understand the relationship patterns between the performer and relatives, commissioners, and audiences. The obtained data were processed through the concept of habitus, arena, capital, and practices. Wayang performance management was analysed through the concept of arena and narrative analysis. The realm of Wayang JÃ¨kdong performance can be seen as a practice within and for East Java collective community that contains cultural, economy, sociopolitics, and symbolic struggles. According to the result, Wayang JÃ¨kdong performative space is a social arena tight with celebrative tradition in East Java society. Celebrative tradition is maintained due to the belief system and strong social solidarity within the aforementioned society. Wayang JÃ¨kdong performance is still solid through the support of the commisioners, especially in its close relation to celebration. Some models of capital management in performing wayang are: (1) nyalap-nyaur model (giving-returning the donation in-natura)